Testing the applicability of soil erodibility nomogram for some tropical soils - Vanelslande, A.; Rousseau, P.; Lal, R.; Gabriels, D.; Ghuman, B.S. (1984)
Soil erodibility measurements using field runoff plots were made for three contrasting soils in Nigeria. Field experiments were conducted over a period of 3 years from 1980 to 1983. The soil at Onne in eastern Nigeria is developed on coastal sediments and is classified as a paleudult. The soil at Ikom derived from basalt is a rhodustalf, and that at Jos on basement complex is an oxic paleustalf. Three runoff plots, each measuring 25 m x 4 m, with appropriate collection tanks and multidivisor system were established at each site. Rainfall intensity was monitored for each experimental site using a daily recording raingauge. Also monitored were the initial soil properties and their alteration over the 3-year period. Estimates of soil erodibility were made using the nomogram developed by Wischmeier et al. (1971). Field measurements indicate soil erodibility to be 0.015, 0.04 and 0.04 (in SI units) for Ikom, Onne and Jos soils, respectively. Soil erodibility as estimated from the nomogram is 0.039, 0.025 and 0.18 for Ikom, Onne and Jos respectively. The considerable differences between the measured and estimated values of soil erodibility indicate the necessity for appropriate modifications to adapt this nomogram for tropical soils.